Subtropical lichens from the Afromontane can display rapid photosynthetic acclimation to simulated climate change - N.T. NDHLOVU; T.N. KHUZWAYO; F.V. MINIBAYEVA; R.P. BECKETT (Photosynthetica)
Afromontane forests are an important part of the KwaZulu Natal region of southern Africa, having a distinctive flora with a high proportion of endemic species, and lichens are keystone members. Unlike other continental areas, KwaZulu Natal climate change is predicted to increase rainfall and cloudiness. In the present study, hydrated Afromontane lichens from both exposed and shaded microhabitats were given either constant [100 µmol(photon) m-2 s-1] or fluctuating [0, 200, 0 µmol(photon) m-2 s-1] light for 8 h a day for 3 d and changes monitored in nonphotochemical quenching (NPQ) and rates of photosynthetic electron transport. In sun but not shade collections, NPQ strongly increased following treatment with constant and fluctuating light. It seems likely that CO2 fixation may be reduced in moist thalli, and the increase in NPQ may reduce ROS formation during exposure to light while hydrated. Sun lichens can readily modify their NPQ in response to increased cloudiness and rainfall expected in KwaZulu Natal.